Thermodynamic evaluation of lithium recovery and freshwater production by sustainable hydrate-based desalination from brine solutions - Sol Geo Lim; Chang Yeop Oh; Hye Rim Choi; Donghyun Moon; Chiho Sung; Sun Ha Kim; Kongtae Ra; Minjun Cha; Ji-Ho Yoon (Desalination, 2025)

Experimental and computational insights into sustainable lithium recovery and freshwater production via CO2 hydrate-based desalination - Sol Geo Lim; Donghyun Moon; Chang Yeop Oh; Hye Rim Choi; Chiho Sung; Sun Ha Kim; Kongtae Ra; Minjun Cha; Ji-Ho Yoon (Chemical Engineering Journal, 2025)

Sustainability assessment of hydrochemical and microbiological disturbances in shallow aquifer by thermal utilization - Jaeyeon Kim; Ji-Young Baek; Hye-na Ko; Dugin Kaown; Hae-Rim Oh; Kang-Kun Lee (Groundwater for Sustainable Development, 2023)

COCH-related autosomal dominant nonsyndromic hearing loss: a phenotype–genotype study - Kyung Seok Oh; Daniel Walls; Sun Young Joo; Jung Ah Kim; Jee Eun Yoo; Young Ik Koh; Da Hye Kim; John Hoon Rim; Hye Ji Choi; Hye-Youn Kim; Seyoung Yu; Richard J. Smith; et al. (Human Genetics, 2022)

Differential genetic diagnoses of adult post-lingual hearing loss according to the audiogram pattern and novel candidate gene evaluation - John Hoon Rim; Byunghwa Noh; Young Ik Koh; Sun Young Joo; Kyung Seok Oh; Kyumin Kim; Jung Ah Kim; Da Hye Kim; Hye-Youn Kim; Jee Eun Yoo; Seung-Tae Lee; Jin Woong Bok; et al. (Human Genetics, 2022)
Ski-slope hearing loss (HL), which refers to increased auditory threshold at high frequencies, is common in adults. However, genetic contributions to this post-lingual HL remain largely unknown. Here, we prospectively investigated deafness-associated and novel candidate genes causing ski-slope HL. We analyzed 192 families with post-lingual HL via gene panel and/or exome sequencing. With an overall molecular diagnostic rate of 35.4% (68/192) in post-lingual HL, ski-slope HL showed a lower diagnostic rate (30.7%) compared with other conditions (40.7%). In patients who showed HL onset before the age of 40, genetic diagnostic probability was significantly lower for ski-slope HL than for other conditions. Further analysis of 51 genetically undiagnosed patients in the ski-slope HL group identified three variants in delta-like ligand 1 ( DLL1 ), a Notch ligand, which presented in vitro gain-of-function effects on Notch downstream signaling. In conclusion, genetic diagnostic rates in post-lingual HL varied according to audiogram patterns with age-of-onset as a confounding factor. DLL1 was identified as a candidate gene causing ski-slope HL.

A biology-driven receptor model for daily pollen allergy risk in Korea based on Weibull probability density function - Kyu Rang Kim; Mijin Kim; Ho-Seong Choe; Mae Ja Han; Hye-Rim Lee; Jae-Won Oh; Baek-Jo Kim (International Journal of Biometeorology, 2017)

Diagnostic usefulness of the GenoType MTBDR plus assay for detecting drug-resistant tuberculosis using AFB smear-negative specimens with positive TB-PCR result - Young Seok Lee; Hye-Rim Kang; Si-Hyeong Lee; Yunmi Kim; Mi-Yeong Kim; Jeong Hwan Shin; Jae Young Moon; Hyun-Kyung Lee; So Young Park; Eun-Kyung Mo; Yong Bum Park; Soo-Yoon Moon; et al. (Infectious Diseases, 2016)

Purification and Anticoagulant Activity of a Fucoidan from Korean Undaria pinnatifida Sporophyll - Woo-Jung Kim; Sung-Min Kim; Hyun-Guell Kim; Hye-Rim Oh; Kyung-Bok Lee; Yoo-Kyung Lee; Yong-Il Park (Algae, 2007)